Mapping the Intellectual Structure of Mobile Payment Research: A Bibliometric Analysis - Sharma, Prashant; Sharma, Saurabh (SAGE open, 2023)
Mobile payment has evolved over time and its adoption and usage have proliferated in the new normal subsequent to the COVID-19 pandemic. This study aims to (1) evaluate the performance and (2) map the body of knowledge in order to (3) chart the avenues to advance mobile payment research in the new normal. To achieve its aims, this study adopts and implements a bibliometric methodology on a corpus of 455 publications retrieved from the Web of Science to provide a retrospective and a prospective of mobile payment research. Using performance analysis, this study unpacks the productivity and impact of the contributors (i.e., journals, articles, authors, countries, and institutions) to mobile payment research. Using science mapping, this study reveals the foundational themes and topical trajectories in the extant literature dedicated to mobile payment research. The findings from the performance analysis and science mapping are subsequently used to inform the agenda for future research on mobile payment.